INSTRUCTIONAL COMPETENCY IN DIGITAL ECOSYSTEM CULTURE: A SYSTEMATIC REVIEW OF ASSISTANT HEADTEACHERS’ LEADERSHIP - Suwardi, Erna; Taat, Muhamad Suhaimi; Talip, Roslee; Paimin, Mohd Sobrye (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
The rapid digitalisation of education has intensified the demand for leadership practices that go beyond technical adoption to shaping sustainable school cultures. This study conducted a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol and PICo framework to examine how digital ecosystem culture influences the instructional competency of Assistant Headteachers in primary education. A total of 32 peer-reviewed studies published between 2020 and 2025 in Scopus and Web of Science were systematically identified, screened, and thematically analysed. Six interrelated themes emerged: digital competence, professional learning communities, differentiated professional development, socio-technical integration, addressing barriers to digital competency, and networking and collaboration beyond school walls. Collectively, these themes highlight the evolving role of Assistant Headteachers as strategic instructional leaders who must balance technological, pedagogical, and cultural demands. The findings extend theoretical perspectives on distributed and supportive leadership while providing practical insights for leadership training and policy development. This review not only synthesises current evidence but also advances the conceptualisation of Assistant Headteachers as pivotal ecosystem builders, offering a framework that can inform both future empirical research and educational policy reform.